Paraoxonase 3 gene Ala99Ala polymorphism distribution in Beninese three ethnic populations - SEGBO, JULIEN A. GAÉTAN; MISSIHOUN, ANTOINE ABEL HOUMÈNOU; AGBANGLA, CLÉMENT (My University, 2016)
The paraoxonase has anti-atherogenic activity which may be altered by the coding gene polymorphisms. The purpose of this study was to assess the genotypes distribution and allelic frequencies in paraoxonase 3 gene Ala99Ala polymorphism in Beninese different ethnic groups. The paraoxonase 3 gene Ala99Ala polymorphism distribution of 228 subjects from three different populations, was studied respectively using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism technique and compared with those in other word populations. The alleles A and G frequencies were 78.0 percent and 22.0 percent respectively of our study population. The allelic frequencies were 98.0 percent and 2.0 percent respectively of Abomey Calavi population; 67.0 percent and 33.0 percent respectively of Adja ethnic group; 66.0 percent and 34.0 percent respectively of Mahi ethnic group. There were no significant ethnic differences for these allelic frequencies between Adja and Mahi ethnic groups (p > 0.05), but there were significant differences compared to Beninese Abomey-Calavi population and other word populations (p < 0.05). These ethnic variations in PON3 gene polymorphisms distribution can be used as an excellent genetic marker and as the basis for further investigation on the association of this polymorphism with the risk of inflammatory diseases.
Keywords: Single Nucleotide Polymorphism; distribution; Population; Paraoxonase